KEBERMAKNAAN HIDUP PADA MANTAN PECANDU GAME ONLINE: INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS - Syahsena, Sapni; Adri, Zakwan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to see how the picture of the meaning of life in ex addicts of online games. The method used in this study is qualitative with phenomenological approach. Data collection techniques are carried out through semi-structured interviews and the data are analyzed using interpretive phenomenological analysis. Researchers found 5 themes related to the meaning of life in former online gaming addicts, such as the background of online gaming addiction, the impact of online gaming addiction, the process of surviving from online gaming addiction, changes after successfully surviving from online gaming addiction, having no desire to re-addiction to online games.